The Relationship Between Mothers' Knowledge and Attitudes Regarding Local Food Use and Stunting Prevention in the Working Area of the Saitnihuta Public Health Center in 2025 - Mayes Felda Simamora; Nova Sontry Node Siregar; Helprida Sihite; Megasilvia Sinaga; Debora Simamora (Sean Institute, 2025)
Stunting remains a major health problem in Indonesia. Utilizing local foods can be an effective prevention strategy, especially if supported by good maternal knowledge and attitudes. The purpose of this study was to determine the relationship between maternal knowledge and attitudes regarding the use of local foods and stunting prevention. This study used a quantitative approach with a cross-sectional design. A sample of 45 mothers with toddlers was selected purposively. Data were collected using a questionnaire and analyzed using the Chi-Square test. The analysis showed a significant relationship between maternal knowledge and stunting prevention (p = 0.001), as well as a significant relationship between maternal attitudes and stunting prevention (p = 0.003). Mothers with good knowledge and positive attitudes were more likely to take stunting prevention measures. In conclusion, maternal knowledge and attitudes regarding the use of local foods are significantly related to stunting prevention measures. Therefore, ongoing education is needed to increase knowledge and foster positive attitudes in mothers in an effort to reduce stunting rates in the community.